CmABF1 and CmCBF4 cooperatively regulate putrescine synthesis to improve cold tolerance of melon seedlings. Issue 1 (11th February 2022) - Li, Meng; Duan, Xiaoyu; Gao, Ge; Liu, Tao; Qi, Hongyan
Abstract: Low temperatures severely restrict melon seedling growth. However, the mechanisms by which melon adapts to cold stress are poorly understood. Arginine decarboxylase (ADC), a key synthetase, catalyzes putrescine biosynthesis in plants. In this study, we found that CmADC functions as a positive regulator of melon seedling cold tolerance. In addition, two transcription factors, abscisic acid-responsive element (ABRE)-binding factor 1 (CmABF1) and C-repeat binding factor 4 (CmCBF4), directly target CmADC to trigger its expression. Consistently, virus-induced gene silencing (VIGS) of CmABF1 or CmCBF4 downregulated CmADC abundance, decreased putrescine accumulation, and reduced cold tolerance. Furthermore, some other CBF and ABF members show at least partial functional redundancy and complementarity with CmABF1 and CmCBF4. Overall, our work reveals that the ABA, CBF, and polyamine pathways may form a cooperative regulatory network to participate in plant cold stress response.